2014
DOI: 10.1007/s00299-014-1706-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Arabidopsis AtPUB30 resulted in increased tolerance to salt stress during germination

Abstract: The Arabidopsis U-box E3 Ub ligase AtPUB30 participates in the salt stress tolerance as a negative factor in an ABA-independent manner during germination. Based on the in silico expression data, the U-box protein 30 (AtPUB30) from Arabidopsis thaliana was identified as a gene that responds to salt stress. The deduced AtPUB30 protein consists of 448 amino acids with a single U-box motif and five ARM-repeat domains. An in vitro self-ubiquitination assay demonstrated that bacterially expressed AtPUB30 exhibited E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…It appears that challenging Arabidopsis seedlings with ABA or salt stress under continuous light reduces germination efficiencies or cotyledon greening of Col-0 to a greater extent (Reyes and Chua, 2007; Chen et al, 2008; Hwang et al, 2015) compared to long-day conditions (Figure 7; Hu et al, 2013). To tackle the oe-mTERF10 ABA phenotype, we grew Col-0, mterf mutant lines and oe-mTERF10 lines in continuous light and a temperature of 20°C on MS medium (control) and MS medium supplemented with 1 μM ABA, and the phenotypes were scored after 7 days (Figure 9D).…”
Section: Resultsmentioning
confidence: 99%
“…It appears that challenging Arabidopsis seedlings with ABA or salt stress under continuous light reduces germination efficiencies or cotyledon greening of Col-0 to a greater extent (Reyes and Chua, 2007; Chen et al, 2008; Hwang et al, 2015) compared to long-day conditions (Figure 7; Hu et al, 2013). To tackle the oe-mTERF10 ABA phenotype, we grew Col-0, mterf mutant lines and oe-mTERF10 lines in continuous light and a temperature of 20°C on MS medium (control) and MS medium supplemented with 1 μM ABA, and the phenotypes were scored after 7 days (Figure 9D).…”
Section: Resultsmentioning
confidence: 99%
“…MtPUB32 also has high sequence similarity with AtPUB13 , which encodes a U-box-ARM protein that links the flowering time and SA-dependent defense signaling pathways in Arabidopsis [12] (S1 Fig and S1 Table). U-box-ARM protein AtPUB30 acts in salt stress tolerance as a negative factor independent of ABA during seed germination [13], and it is homologous to MtPUB38 (S1 Fig). In rice, the U-box-ARM E3 ligase SPL11 negatively regulates plant cell death and defense[14].…”
Section: Resultsmentioning
confidence: 99%
“…AtPUB13 acts as a node that connects flowering time regulation and salicylic acid (SA)-dependent defense signaling in Arabidopsis [12]. AtPUB30 acts in salt stress tolerance as a negative factor whose activity during germination is ABA independent [13]. The roles of PUBs in response to abiotic stresses have also been shown in other plants.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the pub30‐1 mutant shows salt‐tolerant phenotype only in seed germination stage, whereas there is no significant difference between the pub30‐1 mutant and the wild type in postgerminative growth in response to salt stress (Hwang et al, ). However, in our in vitro (Figure ) and in vivo (Figure ) degradation assay of BKI protein, 10‐day‐old seedlings of WT, pub30‐1 , and MYC‐BKI1 transgenic plants in both genotypes were used because it was very difficult to harvest enough plant sample for protein degradation assay at the seed germination stage.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of PUB30 on salt stress tolerance seems to be limited to the seed germination stage (Hwang et al, ). However, BKI1 positively regulates salt tolerance response not only in the seed germination stage but also in seedling growth stage.…”
Section: Discussionmentioning
confidence: 99%